2017
DOI: 10.1051/epjconf/201716005012
|View full text |Cite
|
Sign up to set email alerts
|

Seismology of Giant Planets: General Overview and Results from theKeplerK2 Observations of Neptune

Abstract: Abstract. For this invited contribution, I was asked to give an overview about the application of helio and asteroseismic techniques to study the interior of giant planets, and to specifically present the recent observations of Neptune by Kepler K2. Seismology applied to giant planets could drastically change our understanding of their deep interiors, as it has happened with the Earth, the Sun, and many main-sequence and evolved stars. The study of giant planets' composition is important for understanding both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Because the oscillation frequencies depend on the planet's density profile, measurements of these frequencies can probe the planet's internal structure. Efforts to detect oscillations with visible photometry, which were apparently successful for Jupiter (Gaulme et al 2011), have not yet been successful for the ice giants (Gaulme 2017;Rowe et al 2017). Friedson (2020) found that for reasonable amplitudes detection of pressure or temperature variations due to ice giant normal modes is not as promising as the prospect of detecting their gravitational influence on an orbiting spacecraft.…”
Section: Overview Of Ring Seismologymentioning
confidence: 99%
“…Because the oscillation frequencies depend on the planet's density profile, measurements of these frequencies can probe the planet's internal structure. Efforts to detect oscillations with visible photometry, which were apparently successful for Jupiter (Gaulme et al 2011), have not yet been successful for the ice giants (Gaulme 2017;Rowe et al 2017). Friedson (2020) found that for reasonable amplitudes detection of pressure or temperature variations due to ice giant normal modes is not as promising as the prospect of detecting their gravitational influence on an orbiting spacecraft.…”
Section: Overview Of Ring Seismologymentioning
confidence: 99%
“…Because the oscillation frequencies depend on the planet's density profile, measurements of these frequencies can probe the planet's internal structure. Efforts to detect oscillations with visible photometry, which were apparently successful for Jupiter (Gaulme et al 2011), have not yet been successful for the ice giants (Rowe et al 2017;Gaulme 2017). Friedson (2020) found that for reasonable amplitudes, detection of pressure or temperature variations due to ice giant normal modes is not as promising as the prospect of detecting their gravitational influence on an orbiting spacecraft.…”
Section: Overview Of Ring Seismologymentioning
confidence: 99%